Iklan Tematik Futuristik: “Sasa Tepung Bumbu Serbaguna” Dalam Perspektif Simbolisme - Resty Adiyanti, Inka (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Futuristic is a concept, a strange thing, modern, and imagined from a time that will come in the future. This Avant-Garde concept presents a visual or displays that carry a future and modern theme. In early 2021, Sasa used an animated advertising style by carrying a futuristic concept in Cyberpunk style. The study method of data collection carried out in this study was through observation, literature study, and internet research. This study is aimed at criticizing the creativity and symbolic elements of the combination of cyberpunk style on seasoned flour products which generally have the largest target market or consumption dominated by housewives. Based on a series of analysis results, it is concluded that the connotative meanings contained and implied in the advertisement are quite difficult to understand for someone who only watches it once.